2019
DOI: 10.1155/2019/6793090
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Contributing Factors of Low Back Pain among Long Distance Truck Drivers at Modjo Dry Port, Ethiopia: A Cross-Sectional Study

Abstract: Background Low back pain (LBP) is well known as the most common musculoskeletal disorder with the lifetime prevalence of eighty percent. Worldwide, 37% of low back pain was attributable to occupational risk factors. Truck driving is one among the jobs causing occupational LBP. Even though these drivers in Ethiopia run the high risk of occupational injuries and illnesses like drivers elsewhere, the evidence that shows the magnitude and factors that contribute to LBP is a significant shortcoming. Objective To as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
90
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 19 publications
7
90
1
1
Order By: Relevance
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Further, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled towards the life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Many individual studies have reported that the prevalence of musculoskeletal disorders among the adult working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%